1)
![9 {sec}^{2} a - 9ta {n}^{2} a = \\ 1)1 \\ 2)9 \\ 3)8 \\ 4)0 9 {sec}^{2} a - 9ta {n}^{2} a = \\ 1)1 \\ 2)9 \\ 3)8 \\ 4)0](https://tex.z-dn.net/?f=9+%7Bsec%7D%5E%7B2%7D+a+-++9ta+%7Bn%7D%5E%7B2%7D+a+%3D++%5C%5C+1%291+%5C%5C+2%299+%5C%5C+3%298+%5C%5C+4%290)
plz solve this
Answers
Answered by
4
Hii dear ....
HØPE IT HELPS YOU.!! ☺☺
HØPE IT HELPS YOU.!! ☺☺
Attachments:
![](https://hi-static.z-dn.net/files/dd2/655da975e58e725703c416fcde58009b.jpg)
Answered by
1
Hey mate!! HERE is your answer.....
The correct option is 2-9(ans)
PROCESS:-
9sec²A-9tan²A
=9(sec²A-tan²A)
=9(1)
=9
identity used...
Sec²A-tan²A=1
Hope it helps you.
^_^
The correct option is 2-9(ans)
PROCESS:-
9sec²A-9tan²A
=9(sec²A-tan²A)
=9(1)
=9
identity used...
Sec²A-tan²A=1
Hope it helps you.
^_^
Similar questions